Pregunta
upstudy study bank question image url

The graph of \( g(x)=a\left(\frac{1}{5}\right)^{x}-5 \) passes throunti \( (-2 ;-4) \). 7.1 Show that \( \alpha=\frac{1}{25} \) 7.2 Determine the coordinates of the \( x \) intericentof 7.3 Given: \( h(x)=\left(\frac{1}{5}\right)^{x} \) 7.3.1 Determine the equation of \( x^{-1}(x) \), the inverse of \( h \), in the for \( y=\ldots \) 7.3.2 Describe the transformation from. g to h .

Ask by Weber Chen. in South Africa
Feb 18,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

7.1 \( \alpha = \frac{1}{25} \) 7.2 The \( x \)-intercept is at \( (3, 0) \). 7.3.1 The inverse of \( h(x) \) is \( y = -\log_{5}(x) \). 7.3.2 The transformation from \( g(x) \) to \( h(x) \) involves a vertical compression by a factor of \( \frac{1}{25} \) and a downward shift of 5 units.

Solución

Let's solve the problem step by step. ### 7.1 Show that \( \alpha = \frac{1}{25} \) We know that the graph of \( g(x) = a\left(\frac{1}{5}\right)^{x} - 5 \) passes through the point \( (-2, -4) \). This means that when \( x = -2 \), \( g(-2) = -4 \). Substituting \( x = -2 \) into the equation: \[ g(-2) = a\left(\frac{1}{5}\right)^{-2} - 5 = -4 \] Calculating \( \left(\frac{1}{5}\right)^{-2} \): \[ \left(\frac{1}{5}\right)^{-2} = 5^2 = 25 \] Now substituting this back into the equation: \[ g(-2) = a \cdot 25 - 5 = -4 \] Rearranging gives: \[ a \cdot 25 = -4 + 5 \] \[ a \cdot 25 = 1 \] \[ a = \frac{1}{25} \] Thus, we have shown that \( \alpha = \frac{1}{25} \). ### 7.2 Determine the coordinates of the \( x \)-intercept The \( x \)-intercept occurs when \( g(x) = 0 \). We can set the equation to zero and solve for \( x \): \[ 0 = \frac{1}{25}\left(\frac{1}{5}\right)^{x} - 5 \] Rearranging gives: \[ \frac{1}{25}\left(\frac{1}{5}\right)^{x} = 5 \] Multiplying both sides by 25: \[ \left(\frac{1}{5}\right)^{x} = 125 \] Since \( 125 = 5^3 \), we can rewrite this as: \[ \left(\frac{1}{5}\right)^{x} = 5^{-3} \] This implies: \[ -x = -3 \quad \Rightarrow \quad x = 3 \] Thus, the coordinates of the \( x \)-intercept are \( (3, 0) \). ### 7.3 Given: \( h(x) = \left(\frac{1}{5}\right)^{x} \) #### 7.3.1 Determine the equation of \( x^{-1}(x) \), the inverse of \( h \) To find the inverse of \( h(x) \), we start with: \[ y = \left(\frac{1}{5}\right)^{x} \] Now, we solve for \( x \): 1. Take the logarithm of both sides: \[ \log(y) = x \log\left(\frac{1}{5}\right) \] 2. Rearranging gives: \[ x = \frac{\log(y)}{\log\left(\frac{1}{5}\right)} \] Thus, the inverse function is: \[ x^{-1}(y) = \frac{\log(y)}{\log\left(\frac{1}{5}\right)} \] In terms of \( y \): \[ y = \left(\frac{1}{5}\right)^{x} \quad \Rightarrow \quad x = -\log_{5}(y) \] So, the equation of the inverse is: \[ y = -\log_{5}(x) \] #### 7.3.2 Describe the transformation from \( g \) to \( h \) The transformation from \( g(x) \) to \( h(x) \) can be described as follows: 1. **Vertical Stretch/Compression**: The function \( g(x) \) is vertically compressed by a factor of \( \frac{1}{25} \) compared to \( h(x) \). 2. **Vertical Shift**: The function \( g(x) \) is shifted down by 5 units compared to \( h(x) \). In summary, the transformation from \( h(x) \) to \( g(x) \) involves a vertical compression by a factor of \( \frac{1}{25} \) and a downward shift of 5 units.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To find \( \alpha \), we can use the point \( (-2, -4) \). Plugging in these values into the equation \( g(x) = a\left(\frac{1}{5}\right)^{x}-5 \): \[ -4 = a\left(\frac{1}{5}\right)^{-2} - 5 \] Solving for \( a \): \[ -4 + 5 = a(25) \] \[ 1 = 25a \Rightarrow a = \frac{1}{25} \] Thus, \( \alpha = \frac{1}{25} \). For the \( x \)-intercept, set \( g(x) = 0 \): \[ 0 = a\left(\frac{1}{5}\right)^{x} - 5 \] Solving gives: \[ a\left(\frac{1}{5}\right)^{x} = 5 \Rightarrow \left(\frac{1}{5}\right)^{x} = 125 \Rightarrow \left(\frac{1}{5}\right)^{x} = \left(\frac{1}{5}\right)^{-3} \] Thus, \( x = -3 \). The coordinates are \( (-3, 0) \). To find the inverse \( h^{-1}(x) \): Let \( y = \left(\frac{1}{5}\right)^{x} \): \[ x = \left(\frac{1}{5}\right)^{y} \Rightarrow \log_{(1/5)}(x) = y \] In exponential form, it becomes \( y = -\log_{5}(x) \). For the transformation from \( g \) to \( h \): We can see that \( g(x) \) is a transformation of \( h(x) \) which includes vertical scaling by \( a \) (a factor of \( \frac{1}{25} \)), a horizontal translation (shifting left or right, defined by the \( x \)-intercept), and a vertical shift downward by 5. So, it’s like taking our \( h(x) \) and shrinking it while also shifting it down!

preguntas relacionadas

Latest Pre Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad